Drug Use, the Drug Environment, and Child Physical Abuse and Neglect. (August 2017) - Freisthler, Bridget; Wolf, Jennifer Price; Wiegmann, Wendy; Kepple, Nancy J.
Although drug use is considered a risk factor for child maltreatment, very little work has examined how the drug environment may affect physical abuse and neglect by parents. Utilizing information from a telephone survey with 2, 597 respondents from 43 cities with valid police data on narcotics incidents, we analyzed the relationship between drug use, drug availability, and child maltreatment using multilevel models. City-level rates of drug abuse and dependence were related to more frequent physical abuse. Parents who use drugs in areas with greater availability of drugs reported more physical abuse and physical neglect. Emotional support was protective of all types of maltreatment. While most child welfare interventions focus on reducing parental drug use in order to reduce child abuse, these findings suggest environmental prevention or neighborhood strengthening approaches designed to reduce the supply of illicit drugs may also reduce child abuse through multiple mechanisms.